DOP64 Pathogenic RIPK1 Mutations Cause Infantile-onset IBD with Inflammatory and Fistulizing Features. (21st January 2022) - Sultan, M; Millman, P; McCourt, B; Kol, N; Lev, A; Matar, M; Barel, O; Shamir, R; Wilschanski, M; Konnikova, L; Somech, R; Shouval, D
Abstract: Background: Genetics plays a key role in the pathogenesis of inflammatory bowel disease (IBD). With the expanding use of next-generation sequencing, >70 different monogenic disorders associated with IBD have been identified, and most of them present in the first years of life. Recently, several patients with severe IBD were identified to harbor pathogenic mutations in Receptor-interacting serine/threonine-protein kinase 1 ( RIPK1 ) gene, which regulates necroptosis, a necrotic cell death mechanism. We present the clinical features, genetic analysis and immune work-up of three patients with infantile-onset IBD resulting from novel RIPK1 mutations. Methods: Whole exome sequencing was performed in three patients with severe infantile-onset IBD, along with sanger sequencing for conformation. Mass cytometry time of flight was conducted for in-depth immunophenotyping, including cytokine secretion analysis following lipopolysaccharide (LPS) or Phorbol myristate acetate with ionomycin (PMA-I), on one of the patient's peripheral blood mononuclear cells, and compared to control subjects and patients with Crohn's disease. Results: All patients, born to consanguineous Muslim families, presented with severe colitis and multiple perianal fistulas in the first months of life, without severe or atypical infections. One of the patients had a partial response to high doses of inlfliximab and azathioprine, while another one failed to respond to adaliumab and later to low dose anakinra, an IL-1 receptor antagonist. Genetic studies identified novel and pathogenic genetic variants in the RIPK1 gene in all patients, that were confirmed by Sanger sequencing. Using mass cytometry time of flight unbiased clustering analysis, we identified peripheral immune dysregulation in one of these patients, characterized by an increase in IFNγ CD8 + T cells along with a decrease in monocytes, dendritic cells and B cells. Moreover, RIPK1-deficient patient's immune cells exhibited decreased IL-6 production in response to LPS across multiple cell types including T cells B cells and innate immune cells. Conclusion: Mutations in RIPK1 should be considered in very young patients presenting with colitis and perianal fistulas. Given RIPK1's role in both immune cells (and specifically in inflammasome activation), and epithelial cells, it is unclear whether immunosuppressive medications (including IL1 blockade) as well as allogeneic hematopoietic stem cell transplantation can suppress or cure the hyper-inflammatory response in these patients. Additional studies in humans are required to better define the role of RIPK1 in regulating intestinal immune responses, and how treatment can be optimized for patients with RIPK1 deficiency.